The efficiency in plaque removal and safety of power brushes over manual toothbrushes a randomized controlled clinical trial - Acab, Maria Carmelette P.; Gener, Rosa Maria Wilhelima D.L.; Santos, Jessica K. (Adviser).
This study aimed to determine the efficiency of powered brushes over manual toothbrushes in removing plaque as well as its safety for use. The subjects were screened for the inclusion criteria and were asked to abstain from brushing their teeth for 24 hours prior to the treatment proper. During the treatment proper, plaque was disclosed before and after toothbrushing. Subjects were asked to brush their teeth with their randomly assigned brushing tool for 3 minutes. The efficiency of toothbrushes in removing plaque was assessed through the difference in plaque indices before and after brushing. Results showed that powered brushes are 1.2 times more effective than manual toothbrushes in removing plaque but is statistically insignificant. Both types of brushes are safe for use.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental plaque; Teeth -- Care and hygiene